Anatomists colony - Valdizán, Hermilio (1919)
Colonial period Peruvian Medicine that imitating, with more will than fortune, and Unanue, Ulloa, and others have tried to pattern highlight to our contemporaries, has remained so foreign to our culture and history as hidden curiosities of tibias a timid and investigations of others, which is not surprising unanimity painful to accept that even today, just as unfair judging criteria, the unauthorized adjectives and statements of CAVIEDES somewhat passionate, foreign reporters, as BOTTONI and PETlT . Certainly a big ignorance characterized, in the eighteenth century, the medical staff of the viceroyalty, and more logical no fact that ignorance, if you remember, before you qualify hard, the conditions under which physicians and surgeons Peruvians were formed the lack of a center of teaching and teachers prepared to do it and yet practical selfishness mediocre, smug for cheap victories in civil practice, looking at each disciple a likely rival, perhaps not characterize his teachings by his allegiance to inspire all knowledge transfer.